2022
DOI: 10.3390/molecules27020572
|View full text |Cite
|
Sign up to set email alerts
|

The Improved Milk Quality and Enhanced Anti-Inflammatory Effect in Acetylserotonin-O-methyltransferase (ASMT) Overexpressed Goats: An Association with the Elevated Endogenous Melatonin Production

Abstract: Background: Transgenic animal production is an important means of livestock breeding and can be used to model pharmaceutical applications. Methods: In this study, to explore the biological activity of endogenously produced melatonin, Acetylserotonin-O-methyltransferase (ASMT)-overexpressed melatonin-enriched dairy goats were successfully generated through the use of pBC1-ASMT expression vector construction and prokaryotic embryo microinjection. Results: These transgenic goats have the same normal phenotype as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…By comparing the high and low fecundity of the dairy goats and sequencing their whole genes, Lai et al have identified some candidate genes related to reproductive traits including non-synonymous exon SNPs in SETDB2 and CDH26 genes ( Lai et al, 2016 ). In the previous study, we have found that the transgenic dairy goats with overexpression of AANAT and ASMT not only had the improved milk quality, but also had stronger anti-inflammatory ability than that of wild type ( Tao et al, 2018 ; Wu et al, 2022 ). AANAT and ASMT are rate limiting enzymes for melatonin synthesis and their gene expressions and activities determine endogenous melatonin production.…”
Section: Discussionmentioning
confidence: 96%
“…By comparing the high and low fecundity of the dairy goats and sequencing their whole genes, Lai et al have identified some candidate genes related to reproductive traits including non-synonymous exon SNPs in SETDB2 and CDH26 genes ( Lai et al, 2016 ). In the previous study, we have found that the transgenic dairy goats with overexpression of AANAT and ASMT not only had the improved milk quality, but also had stronger anti-inflammatory ability than that of wild type ( Tao et al, 2018 ; Wu et al, 2022 ). AANAT and ASMT are rate limiting enzymes for melatonin synthesis and their gene expressions and activities determine endogenous melatonin production.…”
Section: Discussionmentioning
confidence: 96%
“…Investigating the differences in shaping the gut microbiota and regulating metabolism in cow’s milk-based infant formulas, goats’ milk-based infant formulas, and mixed-milk-based infant formulas compared to pasteurized breast milk, their metabolomics identification showed that goats’ milk-based infant formulas mainly emphasized bile acid biosynthesis, arachidonic acid metabolism, and steroid biosynthesis metabolic pathways[34]. To explore the biological activity of endogenous melatonin, melatonin-rich dairy goats overexpressing acetylserotonin-O-methyltransferase (ASMT) were successfully prepared using pBC1-ASMT expression vector and microinjection of prokaryotic embryos, and metabolic analyses revealed that the transgenic goats had a unique arachidonic acid metabolic pattern[35].…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing serum reproductive hormones and ovarian genes of pubertal female goats, we found significant enrichment including estrogen signaling pathway, steroid hormone biosynthesis, and cAMP signaling pathway [33] Investigating the differences in shaping the gut microbiota and regulating metabolism in cow's milk-based infant formulas, goats' milk-based infant formulas, and mixed-milk-based infant formulas compared to pasteurized breast milk, their metabolomics identification showed that goats' milk-based infant formulas mainly emphasized bile acid biosynthesis, arachidonic acid metabolism, and steroid biosynthesis metabolic pathways [34] . To explore the biological activity of endogenous melatonin, melatonin-rich dairy goats overexpressing acetylserotonin-O-methyltransferase (ASMT) were successfully prepared using pBC1-ASMT expression vector and microinjection of prokaryotic embryos, and metabolic analyses revealed that the transgenic goats had a unique arachidonic acid metabolic pattern [35] The intestinal tract is the largest digestive organ in the human body. It is colonized by, and consistently exposed to, a myriad of microorganisms, including bifidobacteria, lactobacillus, Escherichia coli, enterococcus, clostridium perfringens, and pseudomonas [36] .…”
Section: Effect Of Different Feeding Methods On Gut Metabolitesmentioning
confidence: 99%
“…As a result, we believe that these correlations are reliable and without the influence of the aging. We also realized that the overexpression of the AANAT and ASMT in dairy goats increased the melatonin levels in peripheral blood and milk, while improving milk quality [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%